Membangun Komunikasi Personal Melalui Bimbingan Kelompok Teknik Diskusi Terhadap Peserta Didik Yang Cenderung Introvert - Listia, Yeti; Darmawani, Evia; Darma Putri, Ramtia (Science and Education Journal (SICEDU), 2022)
Students with introverted tendencies prefer to be alone and prefer quiet places without crowds. This tendency has an impact on the lack of personal communication by students. Information from the BK Teacher of SMK Negeri 1 Belida Darat there are 3-5 people in each class who are few in communicating, this group can be said to be introverted. It is suspected that to build personal communication of students who tend to be introverted, BK teachers can conduct group guidance on discussion techniques. This study aims to determine the effectiveness of group guidance with discussion techniques in building personal communication of students who tend to be introverted. The method used in this research process is Quantitative Pre-Experiment (Pre-Experiment Design). The population in this study were students of XI TKJ SMK Negeri 1 Belida Darat. Researchers took a sample of 8 students according to the characteristics of children who tend to be introverted. The data collection in this study used a questionnaire. The data analysis technique used is the Wilcoxon test. The results showed that group guidance with discussion techniques was effective in improving students' personal communication. The results of the Wilcoxon test using SPSS.20 showed Z count (2.384) > Z table (1.959) and sig value (0.017) < 0.05. 1. Personal communication of introverted students before group guidance is known to 1 student (12.5%) has high communication skills, while the remaining 7 people (87.5%) are in the medium category, but after being given group guidance with discussion techniques, introverted students' personal communication increased to the high category.